Inovasi Pembelajaran Elektronik dan Tantangan Guru Abad 21 - Ferdinandus Bele Sole; Desak Made Anggraeni (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2018)
[Title: Electronic Learning Innovations and 21st Century Teacher Challenges]. The development of information technology that is very rapid in this century has a very significant impact on the world of education, where, the process of transition from the age of industrialization to the age of knowledge requires every field in life to change very quickly and must be able to adapt quickly. Entering the 21st-century technological advances have entered into various aspects of life, including education. Teachers and students, lecturers and students, educators and students are required to have the ability to teach in this 21st century. A number of challenges and opportunities must be faced by students and teachers in order to survive in the age of knowledge that is coloured by the emergence of various educational innovations. One innovation that is developing quite rapidly is electronic learning (electronic learning) or e-learning. E-learning is distance learning (distance learning) that utilizes computer technology, computer networks and/or the internet. This electronic learning innovation allows learners to learn through computers in their respective places without having to physically go to attend classes/lectures in class. Therefore, educators and prospective educators in the 21st century need to be prepared to be able to adapt to the development of science and technology. Teacher Training Institute (LPTK) as an institution producing prospective educators/teachers needs to equip teachers and prospective teachers to skillfully use technology, especially ICT, because of the challenges of future teachers related to ICT. In an effort to prepare prospective teachers entering the 21st century, STKIP Weetebula as one of the LPTKs in Indonesia seeks to equip its students by including e-learning courses in the curriculum of elementary school teacher education study programs (PGSD).